Linguistic Identity with Special Reference to Western Hindi Dialects - Vishnu, Pallav (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
Linguistic identity is the common bond that people share when they can understand each other in their native tongues, even if they share no other common heritage. Linguistic identity gets trickier when you’re talking about two people who may share linguistic bonds but come from mutually hostile ethnic groups. With racial and ethnic identity, linguistic identity does not exist in isolation; it is frequently yet one more facet of how a person identifies. There’s what we might call “reverse linguistic identity.” As Boas demonstrated over a century ago, everyone has at least three independent identities: race (in the traditional, not the anthropological sense), culture, and language. Language (or linguistic) identity take to mean the speech community with which someone is identified. This is probably always a historical phenomenon, either of birth or of personal choice. Most subjects to personal choice are culture and language, for instance, a given person identifies with, or belongs to a particular culture, and speaks a particular language. These identities may be due to birth or socialization, or they may be the result of a deliberate choice NOT to identify with the language and culture of birth. Linguistic identities are double-edged swords because, while functioning in a positive and productive way to give people a sense of belonging, they do so by defining an “us” in opposition to a “them” that becomes all too easy to demonize. All identity markers of a social group together constitute the “culture” or cultural identity of the social group. Therefore, the loss of one marker does not automatically entails the loss of cultural identity. Given the rich multilingual tradition of India where languages act as facilitators rather than as barriers in communication, one hopes that as linguistic identity. This paper is a case study of the author’s inferences regarding the Western Hindi dialects analysis.